Identification of Endoparasites in the Digestive Tract of Free-Range Chickens (Gallus domesticus) - Najwah, Najwah; Noorasifa, Noorasifa; Muhamat, Muhamat (Jurnal Biologi Tropis, 2025)
This community-based study highlights the health risks associated with free-range farming systems of village chickens (G. domesticus) in Indonesia. The primary aim was to examine the presence of gastrointestinal endoparasites and assess their impact on chicken health and productivity. The method involved macroscopic and microscopic examination of the digestive tract of one village chicken using standard parasitological techniques, including flotation with saturated salt solution. The findings revealed mixed infections by nematode Ascaridia galli and cestode Raillietina spp., both of which are known to disrupt nutrient absorption, cause tissue damage, and reduce growth and egg production. A. galli was identified in the jejunum and its eggs confirmed microscopically, while Raillietina spp. segments were found in the ileum. The results demonstrate that free-range chickens are highly vulnerable to helminth infections due to poor sanitation and environmental exposure. Preventive and routine control measures are essential to maintain poultry health and support rural economic sustainability.